Anticancer activity of a monobenzyltin complex C1 against MDA-MB-231 cells through induction of Apoptosis and inhibition of breast cancer stem cells - Fani, S.; Kamalidehghan, B.; Lo, Kong Mun; Nigjeh, S.E.; Keong, Y.S.; Dehghan, F.; Soori, R.; Abdulla, Mahmood Ameen; Chow, K.M.; Ali, Hapipah Mohd; Hajiaghaalipour, F.; Rouhollahi, E.; et al. (Nature Publishing Group, 2016)
In the present study, we examined the cytotoxic effects of Schiff base complex, [N-(3,5-dichloro-2-oxidobenzylidene)-4-chlorobenzyhydrazidato](o-methylbenzyl)aquatin(IV) chloride, and C1 on MDA-MB-231 cells and derived breast cancer stem cells from MDA-MB-231 cells. The acute toxicity experiment with compound C1 revealed no cytotoxic effects on rats. Fluorescent microscopic studies using Acridine Orange/Propidium Iodide (AO/PI) staining and flow cytometric analysis using an Annexin V probe confirmed the occurrence of apoptosis in C1-treated MDA-MB-231 cells. Compound C1 triggered intracellular reactive oxygen species (ROS) production and lactate dehydrogenase (LDH) releases in treated MDA-MB-231 cells. The Cellomics High Content Screening (HCS) analysis showed the induction of intrinsic pathways in treated MDA-MB-231 cells, and a luminescence assay revealed significant increases in caspase 9 and 3/7 activity. Furthermore, flow cytometric analysis showed that compound C1 induced G0/G1 arrest in treated MDA-MB-231 cells. Real time PCR and western blot analysis revealed the upregulation of the Bax protein and the downregulation of the Bcl-2 and HSP70 proteins. Additionally, this study revealed the suppressive effect of compound C1 against breast CSCs and its ability to inhibit the Wnt/β-catenin signaling pathways. Our results demonstrate the chemotherapeutic properties of compound C1 against breast cancer cells and derived breast cancer stem cells, suggesting that the anticancer capabilities of this compound should be clinically assessed.